The Impact of COVID-19 on Psychiatric Emergency and Inpatient Services in the First Month of the Pandemic in a Large Urban Mental Health Hospital in Ontario, Canada - Kim, Helena K.; Carvalho, Andre F.; Gratzer, David; Wong, Albert H. C.; Gutzin, Shayla; Husain, M. Ishrat; Mulsant, Benoit H.; Stergiopoulos, Vicky; Daskalakis, Zafiris J. (Frontiers in Psychiatry, 2021)
The World Health Organization characterized COVID-19 (coronavirus disease 2019) as a pandemic on March 11th, 2020 (WHO). Within a couple of days, all Canadian provinces announced the implementation of social distancing measures. We evaluated the immediate effect of COVID-19 on psychiatric emergency and inpatient services in Canada’s largest psychiatric hospital in the first month of the pandemic. We extracted data from the electronic medical records of the Center for Addiction and Mental Health (CAMH) in Toronto, Canada. We compared emergency department (ED) visits, inpatient occupancy rates, and length of stay in March 2019 and March 2020, and during the first and second half of March 2020. There was a decrease in the number of ED visits and inpatient occupancy rates in March 2020 compared to March 2019. There was also a significant decrease in the number of ED visits and inpatient occupancy rates in the second half of March 2020 compared to the first half, suggesting an immediate decrease in the use of hospital-based psychiatric services during the COVID-19 pandemic. Future studies will need to assess whether this decrease will be followed by a return to baseline or an increase in need for these services.